2017
DOI: 10.1103/physrevd.96.075028
|View full text |Cite
|
Sign up to set email alerts
|

Hadronic resonances with exotic electric charge

Abstract: We classify the meson and baryon long lived resonances that may exist if quarks with electric charge 5/3 and −4/3 (in units of |e|) predicted by some 3-3-1 models do exist. Some of these exotic resonances have the usual electric charges or ±(3, 4, 5), and the lightest ones decaying only into leptons plus known resonances. We propose another heavy SU (3) H global symmetry under which hadrons involving only exotic quarks can be constructed.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…On the other hand, it has been observed that in the m331 and the 331HL models (both with β = − √ 3 and X = 0) there is one quark with electric charge 5/3 and two with −4/3 (in units of |e|). Hence it is possible the existence of a replica of the flavor SU (3) F symmetry of the light quarks u, d, s but now with the heavy quarks J, j 1 , j 2 which would imply the existence of hadrons with exotic quarks [93]. It means that SU (3) F → SU (3) H making u, d, s → J, j 1 , j 2 .…”
Section: B Do Exotic Bound States Exist?mentioning
confidence: 99%
“…On the other hand, it has been observed that in the m331 and the 331HL models (both with β = − √ 3 and X = 0) there is one quark with electric charge 5/3 and two with −4/3 (in units of |e|). Hence it is possible the existence of a replica of the flavor SU (3) F symmetry of the light quarks u, d, s but now with the heavy quarks J, j 1 , j 2 which would imply the existence of hadrons with exotic quarks [93]. It means that SU (3) F → SU (3) H making u, d, s → J, j 1 , j 2 .…”
Section: B Do Exotic Bound States Exist?mentioning
confidence: 99%
“…The CMDM of the top quark has already been studied in the context of an early version of the 331 model [9], and more recently the contributions to the electron and muon anomalous MDM were studied in the RM331 [40] and another 331 realization [41]. In this work we present a study on the contributions of the RM331 to the top quark CMDM and CEDM.…”
Section: Introductionmentioning
confidence: 97%
“…The CMDM of the top quark has already been studied in the context of an early version of the 331 model [9], and more recently the contributions to the electron and muon anomalous MDM were studied in the RM331 [40] and another 331 realization [41]. In this work we present a study on the contributions of the RM331 to the top quark CMDM and CEDM.…”
Section: Introductionmentioning
confidence: 98%